2015
DOI: 10.1007/s11751-015-0225-3
|View full text |Cite
|
Sign up to set email alerts
|

Fibular head transfixion wire and its relationship to common peroneal nerve: cadaveric analysis

Abstract: Proximal tibio-fibular joint is routinely stabilised during leg lengthening, peri-articular fractures and deformity corrections of tibia. Potential injury to the common peroneal nerve at the level of the fibula head/neck junction during wire insertion is a recognised complication. Previous studies have mapped the course of the common peroneal nerve and its branches at the level of the fibular head, and guidelines are published regarding placement of proximal tibial wires. This study aims to relate the course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
3
4
0
Order By: Relevance
“…[14][15][16] We have found that the distance from the tip of the styloid process of the fibula to the nerve as it winds around the neck was 32.3 mm (range 20-50 mm). This finding was similar quoted by the following authors as mentioned in Table 3.This finding concurs with Rupp et al 17 and Dearden et al 5 and same as Ryan et al 6 . In case small metaphyseal fragments, need of drop wires are essential.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…[14][15][16] We have found that the distance from the tip of the styloid process of the fibula to the nerve as it winds around the neck was 32.3 mm (range 20-50 mm). This finding was similar quoted by the following authors as mentioned in Table 3.This finding concurs with Rupp et al 17 and Dearden et al 5 and same as Ryan et al 6 . In case small metaphyseal fragments, need of drop wires are essential.…”
Section: Discussionsupporting
confidence: 92%
“…The distance of the nerve behind the fibula at the widest AP diameter was 25 mm (range 16-35 mm) from the anterior aspect of the fibula which was similar to 24.5 mm as reported by Dearden et al 5 In nine of twenty specimens, the nerve was touching and lying in the posterior border of fibula at its maximum AP diameter. If wire is inserted in posterior aspect of fibula there is a risk of injury to CPN.…”
Section: Specimensupporting
confidence: 86%
See 2 more Smart Citations
“… 3 For excision of an intramedullary lesion of the fibular head and neck, a safe zone is observed in the anterior half of the proximal 20 mm of the fibula head that would avoid injury to the peroneal nerve. 4 However, creation of this bone window may damage the insertions of the lateral collateral ligament, popliteofibular ligament, and biceps femoris tendon or cause avulsion fractures of the fibular head. The purpose of this Technical Note is to report the details of endoscopic curettage of a bone cyst of the fibular head.…”
mentioning
confidence: 99%